Hepatic and portal venous Doppler waveforms and flow velocities in normal pregnancy - Bozgeyik, Zulkif; Ozdemir, Huseyin; Kocakoc, Ercan; Simsek, Mehmet (Int Scientific Literature, Inc, 2009)
Background: Although the flow velocities of portal veins (PV) and flow patterns of hepatic veins (HV) during pregnancy were evaluated in the literature, changes in PV flow pattern during pregnancy have not been assessed. The aim of this study was to detect changes in HV and PV flow velocities and patterns during pregnancy. Material/Methods: One hundred sixty-three healthy pregnant women aged 17- 42 years-old (mean: 26.9+/-5.1) were included in the study. Twenty-seven were in the first trimester (group 1), 89 in the second trimester (group 2), and 47 in the third trimester (group 3). Maximum and minimum flow velocities and waveforms were obtained from the hepatic vein (HV) and the main portal vein (PV) of the subjects. The flow patterns were recorded as monophasic, biphasic, and triphasic waveforms. Results: Maximum flow velocity of PV was higher in group 1 than in groups 2 and 3 (p<0.05). Although some subjects had a monophasic flow pattern of the PV, a biphasic flow pattern was prominent in all groups. A triphasic PV waveform was not observed in any of the groups. In the HV the triphasic waveform was prominent in the first trimester and biphasic in the second and third trimesters. Conclusions: When evaluating physiological changes in pregnancy, flow pattern changes of the HV and flow velocity changes of the PV may be accepted as sensitive parameters and may be indicators of physiological alterations related to pregnancy.
Keywords: portal vein; hepatic vein; pregnancy; Doppler ultrasound